Regulating Li+ Transport and Interfacial Stability with Zwitterionic COF Protective Layer Towards High-Performance Lithium Metal Batteries - Rong, Liya; Han, Yifeng; Zhang, Chi; Yao, Hongling; He, Zhaojun; Wang, Xianbao; Guo, Zaiping; Mei, Tao (Nano-Micro Letters, 2026)
The sluggish Li+ migration kinetics and unstable electrode/electrolyte interface severely hinder the commercial application of high-performance lithium metal batteries (LMBs). Herein, an artificial protective layer is constructed using zwitterionic covalent organic framework (Z-COF) simultaneously containing sulfonate and ethidium groups, aiming to facilitate rapid, uniform Li+ transport and stabilize anode interface. The sulfonate groups with high lithiophilicity provide abundant hopping sites for fast Li+ diffusion. The ethidium cations immobilize TFSI− and solvent molecules by ion–dipole interactions, which accelerate the dissociation of LiTFSI and Li+ desolvation. Moreover, the monodispersed zwitterionic units coupling with ordered micropore structures in Z-COF create exclusive Li+ migration channels, modulate homogeneous space charge distribution, kinetically facilitating uniform Li+ deposition. Experiments and theoretical calculations indicate that C–F and S–N bonds of TFSI− exhibit enhanced cleavage susceptibility driven by electrostatic attraction, realizing a LiF/Li3N-rich electrolyte/electrode interface. The designed Z-COF protection layer enables Li|Li symmetrical cells stable cycling over 6300 h at 2 mA cm−2/2 mAh cm−2. The Z-COF@Li|LiFePO4 (LFP) full cells deliver high-capacity retention of 85.2% after 1000 cycles at 8 C. The assembled Z-COF@Li|LFP pouch cells demonstrate a lifespan of more than 240 cycles. This work provides fresh insights into the practical application of zwitterionic COF in next-generation LMBs. Highlights: 1 Ethidium cations acted as “anion capturers” to immobilize TFSI−, which rendered the C-F and S-N bonds prone to cleavage, facilitating the formation of LiF/Li3N-rich solid electrolyte interphase. 2 Ion–dipole interaction between ethidium groups and dimethoxyethane/dioxolane, boosting Li+ desolvation. 3 Sulfonate groups exhibited an ion-sieving effect that selectively attracted Li⁺ while excluding TFSI⁻, promoting LiTFSI dissociation and accelerating Li+ migration.